KAJIAN PEMASARAN RUMPUT LAUT (Eucheuma Cottoni) (Studi Kasus Desa Tanjung, Pademawu, Pamekasan) - Maftuhah, -; Zuhriyah, Amanatuz (Program Studi Agribisnis Fakultas Pertanian Universitas Trunojoyo Madura., 2013)
Pamekasan, have great potential for the development of seaweed farming. The aims of this study are to know: marketing channels and marketing margins. The method of sampling was done by using incidental sampling and snowball sampling. Mean while, the methods of collecting data through observations, distributing questionnaires, interviews, library research and documentation. Â Â Â Â Data analysis using analysis of R/C ratio to determine the feasibility of the business and margin analysis to determine the efficiency of marketing. The results showed that a). seaweed farming are viable with R/C ratio 1.151 for the wet sales and 1.77 for the dry sales. B) there are two seaweed marketing channels, first: farmers â middlemen â plant collectors â factories, second: farmers â plant collectors â factories. The analysis of marketing margins, showed that marketing channels of wet seaweed was inefficient, while marketing channels of dried seaweed was efficient.